2007
DOI: 10.1007/s00267-007-9004-3
|View full text |Cite
|
Sign up to set email alerts
|

Assessing and Mitigating the Effects of Windblown Soil on Rare and Common Vegetation

Abstract: Acting under the auspices of the US Endangered Species Act, we quantified wind erosion and its effects on rare and common plant species on a semi-arid military installation in Hawaii. Our goal was to develop management strategies, based on local data, to aid the conservation of rare and common indigenous plants and their habitats. We collected windblown soil coming off of roads and other disturbed soils to assess likely impacts to plants occurring at certain heights and distances from disturbed surfaces. We th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Though the other measures of reproduction (i.e., number of plant seeds and plant seed weight) were not statistically significant, the overall pattern of decreasing reproduction with increasing dust deposition strongly suggests that dust has a negative impact. Interestingly, Gleason et al (2007) found that windblown soil had no significant impact on either rare or common plants beyond a distance of 40 m from a road in Hawaii. In our study, no plants grew within 100 m of the road, and we found that dust impacted fruit set regardless of distance.…”
Section: Effects Of Dust Deposition On Reproductionmentioning
confidence: 98%
“…Though the other measures of reproduction (i.e., number of plant seeds and plant seed weight) were not statistically significant, the overall pattern of decreasing reproduction with increasing dust deposition strongly suggests that dust has a negative impact. Interestingly, Gleason et al (2007) found that windblown soil had no significant impact on either rare or common plants beyond a distance of 40 m from a road in Hawaii. In our study, no plants grew within 100 m of the road, and we found that dust impacted fruit set regardless of distance.…”
Section: Effects Of Dust Deposition On Reproductionmentioning
confidence: 98%
“…They are mostly deposited by wet deposition of fine aerosols (Reisinger 1990;Smith 1990;Adachi and Tainosho 2004;Gleason et al 2007). Near sources of heavy metals, concentrations are high on foliage and in litter, eventually contaminating the soil surface layers.…”
Section: Heavy Metalsmentioning
confidence: 99%